Highly Efficient and Stable CdZnSeS/ZnSeS Quantum Dots for Application in White Light-Emitting Diode - Chen, Xi; Li, Jingzhou; Zhong, Yichi; Li, Xin; Pan, Mingzhong; Qi, Hongxing; Dong, Hongxing; Zhang, Long (Frontiers in Chemistry, 2022)
Semiconductor quantum dots (QDs) are a promising luminescent phosphor for next generation lightings and display. In particular, QDs-based white light-emitting diodes (WLED) are considered to be the candidate light sources with the most potential for application in displays. In this work, we synthesized quaternary/ternary core/shell alloyed CdZnSeS/ZnSeS QDs with high bright emission intensity. The quantum dots show good thermal stability by performing high temperature-dependent experiment range from 295 K to 433 K. Finally, the WLED based on the CdZnSeS/ZnSeS QDs exhibits a luminous efficiency (LE) of 28.14 lm/W, an external quantum efficiency (EQE) of 14.86 %, and a warm bright sun light close to the spectrum of daylight (CIE coordinates 0.305, 0.371). Moreover, the PL intensity, LE, EQE, and CCT of as-prepared QD-WLED remained relatively stable with only slight changes in luminescence stability experiment.